Epidemiology of Fascioliasis in Kermanshah Province, Western Iran - Arezoo BOZORGOMID; Naser NAZARI; Eshrat Beigom KIA; Mehdi MOHEBALI; Homa HAJARAN; Peyman HEYDARIAN; Yazdan HAMZAVI; Sara NEMATI; Mojgan ARYAEIPOUR; Mohamad Bagher ROKNI (Tehran University of Medical Sciences, 2018)
Background: We aimed to determine the prevalence of fasciolosis in the definitive hosts (human and livestock) and intermediate (Lymnaea snails) hosts in Kermanshah Province, western Iran from 2014-2016. Methods: The study on animals was descriptive and retrospective one. All daily records of animals slaughtered in the abattoirs were analyzed. For the study of human fascioliasis, 975 serum samples were collected from different parts of Kermanshah Province and analyzed using ELISA based on excretory-secretory antigens. Moreover, 4400 Lymnaea snails were collected from 25 habitats. The snails were identified and examined for presence of cercariae by shedding method. Results: Fasciolosis was diagnosed in 1.7% of slaughtered animals, which was significantly greater than the other species (P<0.005). There was significant difference (P<0.001) between the prevalence of fasciolosis and seasonal pattern. As for human cases, five cases (0.5%) were positive for fascioliasis. Regarding the seropositivity to fasciolosis, no significant differences were found for age groups, sex, level of education and occupation. No Fasciola infection was seen in snails of the family Lymnaeidae. Conclusion: The prevalence of Fasciola parasite was lower compared to other provinces. This is probably due to sequential decline in rainfall and hot climate that makes conditions difficult for the snail intermediate host snails and the larval stages of fasciolid trematodes. The habitual food of people is another important point.